The Effect of Audit Tenure and Audit Rotation on Audit Quality in Companies Listed on the Stock Exchange - Karno, Ahmad; Aulia, Aulia; Panorama, Maya; Rafli Aldiansya, M. (CV. Lafadz Jaya, 2022)
This study aims to determine how audit tenure and audit rotation affect audit quality in companies listed on the Indonesia Stock Exchange in 2019-2020. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2020. Sampling in this study used a purposive sampling method. The data used in this study is secondary data in the form of the Annual Financial Statements of companies listed on the Indonesia Stock Exchange in 2019-2020. The data collection technique used in this research is documentation, namely collecting, recording, and reviewing secondary data in the form of financial reports.